Penerapan Sistem Informasi Akuntansi Penjualan dengan Software Accurate untuk Meningkatkan Efisiensi Proses Penjualan: (Studi Kasus : PT. Karya Mitra Tehnik) - Sinta Dewi Permata Ning Tyas; Aji Prasetyo (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to find the efficiency of the sales process through the application of Accurate software at PT. Karya Mitra Tehnik, with the hope of enabling more measurable operational effectiveness improvements. The subjects used in this study were the marketing manager and the accounting team, while the object of the study was the sales accounting information system using Accurate software at PT. Karya Mitra Tehnik. The author used data collection processes such as interviews, observations, and documentation. The analysis techniques used were data collection, data reduction, data presentation, and data conclusion. The results of the study indicate that PT. Karya Mitra Teknik has implemented the Accurate software application. To improve sales efficiency using the Accurate software, PT. Karya Mitra Teknik utilizes the features available in the Accurate software application, including the Sales Feature, Accounts Receivable & Customer Reports, and Sales Reports. The implementation of the Accurate software application has been beneficial in improving sales process efficiency and has also significantly contributed to enhancing the accuracy of financial reports.